2020
DOI: 10.1021/acs.jproteome.0c00273
|View full text |Cite
|
Sign up to set email alerts
|

The Discovery of a Putative Allosteric Site in the SARS-CoV-2 Spike Protein Using an Integrated Structural/Dynamic Approach

Abstract: SARS-CoV-2 has caused the largest pandemic of the twenty-first century , threatening the life and economy of all countries in the world. The identification of novel therapies and vaccines that can mitigate or control this global health threat is among the most important challenges facing biomedical sciences. To construct a long-term strategy to fight both SARS-CoV-2 and other possible future threats from coronaviruses, it is critical to understand the molecular mechanisms underlying the virus action. The viral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
86
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(91 citation statements)
references
References 61 publications
2
86
0
Order By: Relevance
“…Long-duration modeling can also be applied to in silico screening of molecules that could inhibit the S RBD-ACE2 interaction 8,9,33 . These may be antibodies, peptides or small molecules that either bind directly to the interaction surface or act allosterically to stabilize S RBD in a conformation with low ACE2 binding affinity.…”
Section: Application Of Millisecond-scale MD Simulation To Design Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…Long-duration modeling can also be applied to in silico screening of molecules that could inhibit the S RBD-ACE2 interaction 8,9,33 . These may be antibodies, peptides or small molecules that either bind directly to the interaction surface or act allosterically to stabilize S RBD in a conformation with low ACE2 binding affinity.…”
Section: Application Of Millisecond-scale MD Simulation To Design Ofmentioning
confidence: 99%
“…Our findings reveal that free S RBD has assumed an optimized ACE2 binding-ready conformation, incurring little entropic penalty for binding, an evolutionary adaptation that contributes to its high affinity for the receptor 6 . We further identified high probability molecular binding interactions that inform both vaccine design and therapeutic development, which may include recombinant ACE2-based spike decoys 7 and/or allosteric S RBD-ACE2 binding inhibitors 8,9 to prevent or arrest infection and thus disease.…”
Section: Introductionmentioning
confidence: 99%
“…This region of S1 is close to recently discovered allosteric modulator region of the S1 protein. 74 Residues at positions 225, 452, and 485 of ACE2 protein are highly coupled with the distal residues of the S1 protein dynamically. Therefore, the mentioned positions of ACE2 play a critical role in information transfer between ACE2 and S1 subunits of the complex.…”
Section: Resultsmentioning
confidence: 99%
“…Of more importance right now would be the theoretical and/or actual elucidation of the structure of the spike protein TM-CT junction region and a comparison with the available hepcidin structures (the Pfam hepcidin entry, PF06446, currently references six PDB structures). Of note, a recent in silico study has reported on a predicted structural similarity and compatibility between hepcidin and an allosteric site in the SARS-CoV-2 spike protein [32].…”
Section: Hepcidin and The Cov Spike Protein Available Structures Andmentioning
confidence: 99%